Instrumented Functional Reach Test Differentiates Individuals at High Risk for Parkinson’s Disease from Controls - Hasmann, Sandra E.; Berg, Daniela; Hobert, Markus A.; Weiss, David; Lindemann, Ulrich; Streffer, Johannes; Liepelt-Scarfone, Inga; Maetzler, Walter (Frontiers in Aging Neuroscience, 2014)
The functional reach test (FR) as a complex measure of balance including limits of stability has been proven to differentiate between patients with Parkinson’s disease (PD) and controls. Recently it has been shown that the instrumentation of the FR (iFR) with a wearable sensor may increase this diagnostic accuracy. This cross-sectional study aimed at investigating whether the iFR has the potential to differentiate individuals with high risk for PD (HRPD) from controls, as the delineation of such individuals would allow for e.g. early neuromodulation. Thirteen PD patients, 13 controls and 31 HRPD were investigated. HRPD was defined by presence of an enlarged area of hyperechogenicity in the mesencephalon on transcranial sonography and either one motor sign or two risk and prodromal markers of PD. All participants were asked to reach with their right arm forward as far as possible and hold this position for 10 seconds. During this period, sway parameters were assessed with an accelerometer worn at the lower back. Extracted parameters which differed significantly between PD patients and controls in our cohort [FR distance (shorter in PD), anterior-posterior (AP) and mediolateral (ML) acceleration (both lower in PD)] as well as JERK which has been shown to differentiate HRPD from controls and PD in a previous study, were included in a model which was then used to differentiate HRPD from controls. The model yielded an area under the curve of 0.77, with a specificity of 85%, and a sensitivity of 74%. These results suggest that the iFR can contribute to an assessment panel focusing on the definition of HRPD individuals.